If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x * 7)(x + -5) = 5x + -37 Reorder the terms for easier multiplication: (7x)(x + -5) = 5x + -37 Remove parenthesis around (7x) 7x(x + -5) = 5x + -37 Reorder the terms: 7x(-5 + x) = 5x + -37 (-5 * 7x + x * 7x) = 5x + -37 (-35x + 7x2) = 5x + -37 Reorder the terms: -35x + 7x2 = -37 + 5x Solving -35x + 7x2 = -37 + 5x Solving for variable 'x'. Reorder the terms: 37 + -35x + -5x + 7x2 = -37 + 5x + 37 + -5x Combine like terms: -35x + -5x = -40x 37 + -40x + 7x2 = -37 + 5x + 37 + -5x Reorder the terms: 37 + -40x + 7x2 = -37 + 37 + 5x + -5x Combine like terms: -37 + 37 = 0 37 + -40x + 7x2 = 0 + 5x + -5x 37 + -40x + 7x2 = 5x + -5x Combine like terms: 5x + -5x = 0 37 + -40x + 7x2 = 0 Begin completing the square. Divide all terms by 7 the coefficient of the squared term: Divide each side by '7'. 5.285714286 + -5.714285714x + x2 = 0 Move the constant term to the right: Add '-5.285714286' to each side of the equation. 5.285714286 + -5.714285714x + -5.285714286 + x2 = 0 + -5.285714286 Reorder the terms: 5.285714286 + -5.285714286 + -5.714285714x + x2 = 0 + -5.285714286 Combine like terms: 5.285714286 + -5.285714286 = 0.000000000 0.000000000 + -5.714285714x + x2 = 0 + -5.285714286 -5.714285714x + x2 = 0 + -5.285714286 Combine like terms: 0 + -5.285714286 = -5.285714286 -5.714285714x + x2 = -5.285714286 The x term is -5.714285714x. Take half its coefficient (-2.857142857). Square it (8.163265305) and add it to both sides. Add '8.163265305' to each side of the equation. -5.714285714x + 8.163265305 + x2 = -5.285714286 + 8.163265305 Reorder the terms: 8.163265305 + -5.714285714x + x2 = -5.285714286 + 8.163265305 Combine like terms: -5.285714286 + 8.163265305 = 2.877551019 8.163265305 + -5.714285714x + x2 = 2.877551019 Factor a perfect square on the left side: (x + -2.857142857)(x + -2.857142857) = 2.877551019 Calculate the square root of the right side: 1.696334583 Break this problem into two subproblems by setting (x + -2.857142857) equal to 1.696334583 and -1.696334583.Subproblem 1
x + -2.857142857 = 1.696334583 Simplifying x + -2.857142857 = 1.696334583 Reorder the terms: -2.857142857 + x = 1.696334583 Solving -2.857142857 + x = 1.696334583 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.857142857' to each side of the equation. -2.857142857 + 2.857142857 + x = 1.696334583 + 2.857142857 Combine like terms: -2.857142857 + 2.857142857 = 0.000000000 0.000000000 + x = 1.696334583 + 2.857142857 x = 1.696334583 + 2.857142857 Combine like terms: 1.696334583 + 2.857142857 = 4.55347744 x = 4.55347744 Simplifying x = 4.55347744Subproblem 2
x + -2.857142857 = -1.696334583 Simplifying x + -2.857142857 = -1.696334583 Reorder the terms: -2.857142857 + x = -1.696334583 Solving -2.857142857 + x = -1.696334583 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.857142857' to each side of the equation. -2.857142857 + 2.857142857 + x = -1.696334583 + 2.857142857 Combine like terms: -2.857142857 + 2.857142857 = 0.000000000 0.000000000 + x = -1.696334583 + 2.857142857 x = -1.696334583 + 2.857142857 Combine like terms: -1.696334583 + 2.857142857 = 1.160808274 x = 1.160808274 Simplifying x = 1.160808274Solution
The solution to the problem is based on the solutions from the subproblems. x = {4.55347744, 1.160808274}
| 14-10x=6x-18 | | 16x-12=8x+8 | | 24-15x=2x+7 | | 14x-16=5x+29 | | 0,3(8-3y)=3,2-0,8(y-7) | | 4p+8=12p-16p | | 9y^2=12x-4 | | 10+5y-y=-2 | | q^2-4q=-10 | | 24x=-12+-3(-9+3x) | | 150x+25y=1200 | | q^2-4q=10 | | 3y+24x=-12 | | x+8=x^2+2x+2 | | -6-6y+y=4 | | 2x+3y+23=0 | | x^2-13x-17=-8x-3 | | 4x-21=2x-3 | | 1023x=(x+500)*500 | | 3x=x+500 | | 8/9×4/1 | | (1500-x)-1200-y=3x-y | | -3x^2+12x+17=0 | | x*x+6x=5 | | -3x^2+12x+8=0 | | 22+11y= | | 4+7*7= | | 22+11y=23 | | 5x^2+7x-2400=0 | | y=180-(140-2x) | | y=5sinx+5x | | 3x^2+6x+9x=0 |